Equality between Incivility among Nurses and Psychological Well-being in Three Main Hospitals in Southeast Iraq - Safa M. Karam, Qahtan Q. Mohammed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: It is impossible to emphasize or ignore the widespread problem of incivility behavior in nursing workplaces. To the best of the knowledge of the present studies, no comprehensive research on this subject has been carried out in Iraq. Inconsiderate incivility-behavior in the nursing workplace has never been subjected to exhaustive research, despite its potential impact on the mental health of nurses hailing from various cultural traditions. Methods: In this descriptive research, 250 nurses in three main hospitals in Southeast Iraq were questioned using the nursing incivility scale (NIS) and Ryff's psychological well-being measure (PWB). Results: results indicate that 63.6% of nurses show a moderate, 24% showed a low level, and 12% show a high level of nursing incivility at the workplace (M±SD= 123.01±29.544). Psychological well-being indicates that nurses have low to moderate in which 67.2% of them show moderate level and 32.4% show low level (M±SD= 59.36±11.222). Conclusion: in this study level of nursing incivility at the workplace is the most important factor that can affect the psychological well-being of nurses. This study's conclusions may help build human resource strategies to meet nurses' requirements, reduce workplace incivility, and improve psychological well-being.